Marketing Strategy For Beading Crafts Products Using Social Media In Smp Negeri 2 Na Ix-X Sumberjo - Ade Sri Wahyuni; Yuniman Zebua; Hayanuddin Safri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The purpose of community service is to help knowledge and skills in making handicrafts in the form of beads and also help earn income. Although still in a small scope, the resulting product is already widely known by consumers. And so that students have the knowledge and skills in using social media to train a creative and independent business spirit. The location of this community service is at SMP NEGERI 2 Sumberjo, sub-district. Na IX-X. The target in this PKM is class IX-1 students, totaling 27 students. The method used is observation, interviews and counseling. The aims of this PKM are: 1) beaded bracelet accessories with various colors that can make the bracelet very beautiful. 2) Improve the knowledge and skills of SMP NEGERI 2 SUMBERJO students in creative and entrepreneurship subject matter. 3) Students have an interest and desire to develop a business spirit through social media and online applications. 4) can produce accessories that have selling value and students have motivation by selling online, adding pocket money and helping parents.